BRACHIOPOD-BASED OXYGEN-ISOTOPE THERMOMETER: UPDATE AND REVIEW (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2019)
In the early 1950’s, McCrea and Epstein and co-workers laid the foundation for the oxygen isotope-based thermometers. Many variations of the thermometer have been since formulated based on synthetic and biogenic carbonates. Overall, the use and application of oxygen isotope thermometers must consider and be specific as to the mineralogy, and whether it is synthetic, abiogenic or biogenic carbonate. Here, we propose an updated and refined oxygen-isotope thermometer based on a large database of articulated brachiopods from high to low latitudes, cold to warm and shallow to deep-water regimes. In general, brachiopod-based oxygen isotopes are offset from abiogenic calcite precipitated in thermodynamic equilibrium by about -1 ‰. They maintain this offset and that allows for the determination of robust ambient water temperatures over the full marine spectrum. Thus, the specific brachiopod-based oxygen-isotope thermometer applies, with few exceptions, to most modern articulated brachiopods, and potentially their ancient counterparts, and it is as follows:T°C =17.3750 – 4.2535 (δc-δw) + 0.1473 (δc-δw) 2 (N=578, r 2 = 0.980)Furthermore, it is imperative that mineralogy and taxa be considered for their appropriateness in the application of oxygen isotope thermometers on synthetic, abiogenic and biogenic marine carbonates. Articulated brachiopods are ideal recorders of oceanographic parameters due to their sessile nature, widespread distribution, high abundance in the Paleozoic and Mesozoic, high resilience to most environmental stresses (e.g., climate change - global warming, ocean acidification), and the resistance of the calcite shell – the archive – to post-depositional diagenetic alteration.